Statistical methods for psychology - Howell, David C. (Duxbury Thomson Learning, 2002)
CD-ROM contains: Data sets from text.
Includes bibliographical references (p. 763-772) and index
Keywords: Psychologie; Statistische methoden; aPsychometrics; Statistik; Lehrbuch